2016
DOI: 10.1007/s10549-016-3918-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of race, ethnicity, and BMI on achievement of pathologic complete response following neoadjuvant chemotherapy for breast cancer: a pooled analysis of four prospective Alliance clinical trials (A151426)

Abstract: Purpose Previous studies demonstrated poor response to neoadjuvant systemic therapy (NST) for breast cancer among black women and women who are overweight or obese but this may be due to chemotherapy under dosing. We assessed associations of race, ethnicity and body mass index (BMI) with pathologic complete response (pCR) in clinical trial populations. Methods 1797 women enrolled in four NST trials (CALGB 40601, 40603; ACOSOG Z1041, Z1071) were included. Tumor subtypes were defined by estrogen receptor (ER) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 50 publications
4
35
2
Order By: Relevance
“…Ethnic disparities related to breast cancer in Hispanics might be related to several factors noted previously in the literature including inferior participation of Hispanic women in cancer screening programs [17], prevalence of obesity and comorbidities, inadequate insurance coverage as well as less access, adherence, and possibly response to treatment [18][19][20][21]. Furthermore, prior studies have demonstrated that individuals without health insurance are less likely to have a usual source of health care and less likely to receive preventive services including cancer screening and are more likely to be diagnosed with late stages of cancer [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic disparities related to breast cancer in Hispanics might be related to several factors noted previously in the literature including inferior participation of Hispanic women in cancer screening programs [17], prevalence of obesity and comorbidities, inadequate insurance coverage as well as less access, adherence, and possibly response to treatment [18][19][20][21]. Furthermore, prior studies have demonstrated that individuals without health insurance are less likely to have a usual source of health care and less likely to receive preventive services including cancer screening and are more likely to be diagnosed with late stages of cancer [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…HR-positive, HER2-negative subtype. Another possible explanation is that BMI can affect pCR[18]. However, our analyses did not reveal any relationship between BMI and pathological (complete or partial) response in the patient cohort (data not shown).From a surgeon's perspective, it is important to identify the clinical factors that may impact the outcomes of surgical procedures, not the response to NAC.…”
mentioning
confidence: 81%
“…The data available on the influence of weight on NAC response has been inconsistent. Some studies suggest that OB patients are less likely to have pathologic complete response (pCR) to NAC and are more likely to experience worse disease-free survival (DFS) and overall survival (OS) [17181920], while others showed contradictory results [212223]. There have been few studies focusing on the influence of weight change during NAC on pCR and long-term survival.…”
Section: Introductionmentioning
confidence: 99%